HCI in business, government, and organizations : 5th International Conference, HCIBGO 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: 5th International Conference, HCIBGO 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. (2018) - Unknown
No abstract available